Between Hibah and Waṣiat Wājibah for Non-Muslims: Expansive Legal Interpretations by Indonesian Religious Judges in Inheritance Cases - Hakim, Muhammad Lutfi (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Apart from gender, differences in religious affiliation have often been perceived as negatively impacting the rights of non-Muslims in the practice of family law within Muslim jurisdictions. This article challenges that assumption by presenting recent evidence from the practice of religious courts in Indonesia, specifically in inheritance cases involving testators without heirs. It aims to analyze the legal arguments employed by religious judges in granting the testator’s estate to non-Muslim cognates through hibah (gift). By examining three court verdicts, from the first instance to the cassation level, the author finds that religious judges utilize both juridical and philosophical reasoning to accommodate the rights of non-Muslims via the institution of hibah wājibah (mandatory gift). While the juridical arguments at the first-instance level align with classical fiqh (Islamic jurisprudence), which prescribes allocating the testator’s estate to the bait al-māl (public treasury), higher-level judges deviate from this approach. They adopt an expansive interpretation of hibah provisions, prioritizing societal justice over rigid adherence to classical fiqh rules. Unlike waṣiat wājibah (mandatory will), hibah wājibah offers greater flexibility, as a maximum limit does not constrain it. The author argues that the state’s efforts to encourage religious judges to shift away from rigid classical fiqh references have been gradually successful. This finding carries significant implications for promoting justice and equality among citizens, regardless of their religious affiliation. [Perbedaan afiliasi agama, selain gender, berdampak negatif pada hak yang diterima oleh non-muslim dalam praktik hukum keluarga di yurisdiksi muslim. Artikel ini membantah asumsi ini dengan menyajikan bukti terbaru melalui praktik peradilan agama Indonesia pada kasus pewaris tidak memiliki ahli waris. Untuk itu, artikel ini bertujuan untuk menganalisis argumentasi hukum yang digunakan oleh para hakim agama dalam menyelesaikan kasus tersebut yang melibatkan kerabat non-muslim. Melalui analisis isi terhadap tiga putusan pengadilan agama dari tingkat pertama sampai kasasi, penulis menemukan bahwa para hakim menggunakan argumentasi yuridis dan filosofis untuk mengakomodasi hak-hak non-muslim melalui institusi hibah wajibah. Meskipun argumentasi yuridis para hakim agama pada tingkat pertama kompatibel dengan ketentuan fikih klasik yang memberikan harta peninggalan tersebut ke bait al-māl, namun argumentasi hukum para hakim pada dua tingkat terakhir cenderung mengabaikannya. Mereka menginterpretasikan secara ekspansif ketentuan tentang hibah dengan mempertimbangkan rasa keadilan yang hidup di masyarakat. Pemenuhan hak-hak non-muslim melalui hibah wajibah ini lebih fleksibel, karena tidak memiliki batas maksimal bagian sebagaimana dalam wasiat wajibah. Penulis berargumentasi bahwa upaya negara menjauhkan para hakim agama dari merujuk pada ketentuan fikih klasik berhasil secara bertahap. Temuan ini berimplikasi terhadap keadilan dan persamaan hak antar warga negara, tanpa memandang afiliasi agama.]